SIFAT-SIFAT FISIK DAN SENSORIS PRODUK BUAH HASIL RESTRUKTURISASI NON-TERMAL SELAMA PENYIMPANAN DINGIN [Physical and Sensoric Properties of Restructured Fruit During Refrigerated Storage] - Sri Raharjo; Zaki Utama (Jurnal Teknologi dan Industri Pangan, 2002)
The objective of this experiment was to develop novel restructured products from tropical fruits. A model fruit product was developed using fresh tropical fruits puree (avocado, mango, jackfruit, sapodilla, and soursop) and calcium-alginate gel forming methods (internal setting). As binding system low viscosity alginate  and three different calcium sources (Ca-lactate, Ca-chloride and encapsulated Ca-lactate) were used. Gel forming was conducted  by internal setting and calcium was released under controlled conditions simultaneously throughout the system. The products were  then stored at 4 oC for  9 days. Sensory evaluation indicated that restructured sapodilla with Calactate or encapsulated Ca-lactate (1%) had better taste as compared to product were with Ca-chloride. Different calcium sources had no significant effect on flavor as compared to those of fresh fruit. During refrigerated storage, however, products prepared with soursop and avocado suffered discoloration. Calcium, lactate or encapsulated Ca-lactate produced weaker gel than that of calcium chloride. Restructured fruits that have been stored up 9 days were  still considered acceptable by panelists.